Siblings with Infantile Neuroaxonal Dystrophy - Agarwal, Pulkit; Goswami, Jyotindra Narayan (Journal of Pediatric Neurology, 2020)
A 2 years 3 months male toddler with motor delay and his female sibling with history of marked global developmental regression following an intercurrent febrile illness were both noted to have phospholipase A2G6 (PLA2G6) mutation, confirming the diagnosis of infantile neuroaxonal dystrophy (INAD). This case report attempts to familiarize readers with the pleomorphic presentation of INAD and the role of early clinical identification, examination, and prompt genetic testing in establishing a diagnosis.
Keywords: infantile neuroaxonal dystrophy; PLA2G6 mutation